A VIRTUAL REALITY BALANCE OBSTACLE TRAINING SYSTEM, METHOD AND COMPUTER-READABLE MEDIUM THEREOF - HSU, WEI LI; KANTHA, PHUNSUK (2023)
The present invention provides a virtual reality balance obstacle training system, method and computer readable medium thereof, including a virtual reality device, a dynamic sensor, a balance obstacle training device and a back-end processing device, wherein the subject performs balance obstacle training on the balance obstacle training device, and the balance obstacle training device detects the subject's tilt data and pressure data, and the dynamic sensor detects the subject's sliding data. Furthermore, the back-end processing device controls the virtual reality image displayed to the subject by the virtual reality device according to the sliding data and the tilt data, and calculate the balance obstacle result of the subject based on the sliding data and the pressure data. Therefore, the present invention uses balance obstacle training to effectively improve the balance obstacle of the subject, and can clearly evaluate the physical condition of the subject through the balance disorder result.